2004
DOI: 10.1592/phco.24.2.159.33147
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Performance Characteristics of Valved Holding Chamber and Spacer Devices with a Fluticasone Metered‐Dose Inhaler

Abstract: Spacers and VHC devices available in the United States do not demonstrate equivalent in vitro performance with the fluticasone MDI. The difference between highest and lowest respirable doses in each device category would likely lead to clinically relevant differences in the quantity of fluticasone delivered to a patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…We demonstrated that the use of an in vitro simulation (FVS) method using both tidal and slow maximal inhalation breathing patterns resulted in significant variations in the delivered salbutamol dose when compared with the industry standard cascade impaction method with a constant high flow of 28.3 L/min (Tables 2 and 3). Using standard cascade impaction, no overall effect of spacer volume alone on drug delivery was found, which is consistent with data published in the published work 8–10 . Within both small‐ and large‐volume spacer groups, individual spacer brands such as the Volumatic, Breath‐a‐tech and Lite Aire delivered significantly higher total and respirable outputs compared with the other spacers tested possibly reflecting differences in valve design and construction material, as well as spacer volume.…”
Section: Discussionsupporting
confidence: 86%
“…We demonstrated that the use of an in vitro simulation (FVS) method using both tidal and slow maximal inhalation breathing patterns resulted in significant variations in the delivered salbutamol dose when compared with the industry standard cascade impaction method with a constant high flow of 28.3 L/min (Tables 2 and 3). Using standard cascade impaction, no overall effect of spacer volume alone on drug delivery was found, which is consistent with data published in the published work 8–10 . Within both small‐ and large‐volume spacer groups, individual spacer brands such as the Volumatic, Breath‐a‐tech and Lite Aire delivered significantly higher total and respirable outputs compared with the other spacers tested possibly reflecting differences in valve design and construction material, as well as spacer volume.…”
Section: Discussionsupporting
confidence: 86%
“…Comparison of these results to in vitro deposition data obtained in a similar manner from commercially available spacers revealed that the fine‐particle fraction of fluticasone from this 500‐ml bottle‐spacer was significantly larger than from any non‐valved spacer available in the United States (p> 0.01, Fig. 3) (22).…”
Section: Efficacy Of a Bottle‐spacermentioning
confidence: 65%
“…A final limitation is that a bottle‐spacer has not been extensively studied. However, all available studies to date have reported that this spacer is as effective as control, conventional spacers (16,17,21–23).…”
Section: Limitationsmentioning
confidence: 99%
“…During the assay of fluticasone, the drug was eluted isocratically at a mobile phase flow rate of 1.2 mL/min and monitored with a UV detector operating at 238 nm. The mobile phase for the assay consisted of an acetonitrile and water mixture (65:35 v/v) (Asmus et al, 2004; Steckel and Muller, 1998). The run time for the assay was 10 minutes, and the retention time for fluticasone was 3.9 ± 0.2 min.…”
Section: Methodsmentioning
confidence: 99%